2022
DOI: 10.1051/0004-6361/202243389
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of evolved stars to constrain the internal transport of angular momentum

Abstract: Context. Asteroseismology provides constraints on the core rotation rate for hundreds of low- and intermediate-mass stars in evolved phases. Current physical processes tested in stellar evolution models cannot reproduce the evolution of these core rotation rates. Aims. We investigate the efficiency of the internal angular momentum redistribution in red giants during the hydrogen-shell and core-helium burning phases based on the asteroseismic determinations of their core rotation rates. Methods. We computed ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…According to the extant models, mixing induced by rotation produces a marginal effect on the TDU, while it could modify the 13 C-pocket, after its formation, and the consequent s-process nucleosynthesis. Nevertheless, recent asteroseismic studies of evolved low-mass stars revealed that most of the internal angular momentum is lost before the AGB phase, so that rotation likely does not play a relevant role in the AGB evolution and nucleosynthesis (see, e.g., [21] and references therein). More promising is the hypothesis of mixing induced by internal gravity wave (IGW) generated at the boundary of the convective envelope [22].…”
Section: Boundary Mixing and Extra-mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the extant models, mixing induced by rotation produces a marginal effect on the TDU, while it could modify the 13 C-pocket, after its formation, and the consequent s-process nucleosynthesis. Nevertheless, recent asteroseismic studies of evolved low-mass stars revealed that most of the internal angular momentum is lost before the AGB phase, so that rotation likely does not play a relevant role in the AGB evolution and nucleosynthesis (see, e.g., [21] and references therein). More promising is the hypothesis of mixing induced by internal gravity wave (IGW) generated at the boundary of the convective envelope [22].…”
Section: Boundary Mixing and Extra-mixingmentioning
confidence: 99%
“…[7], and references therein). As a matter of fact, the s-process enhancement observed in normal C stars is mainly due to the 13 C neutron burst, while the 22 Ne source only provides a marginal contribution. The presence of Tc alive ( 99 Tc half-life 2.11 × 10 5 yr) in the atmosphere of C stars is a probe of their intrinsic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Key observational constraints have been obtained for subgiant and red giant stars with the asteroseismic determination of the core rotation rates for a large sample of these evolved stars (Beck et al 2012;Deheuvels et al 2012Deheuvels et al , 2014Deheuvels et al , 2015Deheuvels et al , 2017Di Mauro et al 2016Mosser et al 2012;Gehan et al 2018;Fellay et al 2021). Comparisons with rotating models have then revealed the need for an efficient AM transport mechanism in addition to meridional circulation and transport by the shear instability (Eggenberger et al 2012;Ceillier et al 2013;Marques et al 2013;Eggenberger et al 2017Eggenberger et al , 2019Moyano et al 2022). Detailed asteroseismic studies of the internal rotation for some main-sequence (MS) stars, in particular, for γ Dor pulsators, also suggested that an efficient transport of AM operates in the radiative zones of these stars, similarly to the conclusion obtained for the Sun and evolved stars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transport of angular momentum have been shown to be varying along evolution with an efficient transport during the MS, then a decreasing phase along SGB, and, finally, a new increase during the RGB phase (e.g. Deheuvels et al 2014Deheuvels et al , 2020Spada et al 2016;Eggenberger et al 2019a,b;Moyano et al 2022Moyano et al , 2023. These observational constraints suggest the action of an additional unknown transport of angular momentum whose identification remains an open question.…”
Section: Introductionmentioning
confidence: 99%